Habituation of the Character of Enjoying Reading Through the School Literacy Movement Program in the Lower Grades of Elementary Schools - Oktaviani, Ericha; Kaltsum, Honest Ummi (Jurnal Paedagogy, 2023)
This study aims to describe the implementation of character education fond of reading through the school literacy program for students at SDIT Muhammadiyah Al Kautsar, Kartasura. This study used a descriptive qualitative method with a phenomenological approach. The research subjects were the grade II teacher, the Library Division, and the Vice Principal for Student Affairs. This research instrument used Human Instrument, where this qualitative research determined the focus of research, selected information as data sources, conducts data collection, assessed qualitative data, analyzes data, interpreted data, and made conclusion based on its findings. In qualitative research, besides acting as the main instrument, researchers also used data collection techniques, including observation, interviews, and documentation. The results of this study showed that the application of the character of fond of reading in the School Literacy Movement program was carried out every day during school hours by reading books for 10-15 minutes of reading, then making a core of the task read after that telling or presenting it back. To support school literacy activities, facilities, and infrastructure in the form of reading corners located in classrooms, as well as literacy cards to record the results of students’ independent reading, were provided. Meanwhile, students’ reading interest at SDIT Muhammadiyah Al Kautsar Kartasura was known through the Literacy Card for student visits to the library. The implementation of literacy classes was related to increasing students’ interest in reading because students can take the time to read a little to fulfill literacy cards. If the application of this love of reading can run well and regularly, the student’s interest in reading will also increase.